Is present pharmacy education adapted to needs? Survey results from young practitioner views regarding pharmacy education outcome towards a national reform in Hungary - András Fittler; Gabriella Nagy; Karina M. Füstös; Róbert Gy. Vida; Gábor Rébék-Nagy; István Szabó; István G. Télessy (Elsevier, 2022)
Background: The pharmacist career is constantly adapting to societal and health care needs. The past decade has seen a growing demand for curricular development to align graduation outcome with workforce competencies. Objective: This study aims to identify expectations for both didactic and experiential components of a new curriculum based on young pharmacist practitioner views. Methods: An online survey questionnaire was used in 2019-2020 to evaluate the pharmacy curriculum to detect indicators or key areas which require comprehensive reform. Results: The predominant majority of the 205 study participants recommended reduction in credit hours for Natural Sciences (78.54%) and a similar increase in the Theoretical and Practical Expertise Module (77.9%). Pharmaceutical care, clinical therapeutics and clinical pharmacy competencies should also be more highlighted in the program. Findings indicate the current training does not prepare for problem-solving and daily workplace challenges (72.7%) or for extended pharmacist skills and competencies (71.71%). Results show inconsistency in practical training experience, as all respondents participated in practical training for drug manufacturing and analysis but 61.0% reported no hands-on skills training in a hospital-clinical simulation setting. Indications for practitioner involvement into the natural sciences and biomedical subjects (86.3%) confirm the obvious need for more practice-oriented education. Conclusions: Educational reforms seem to be inevitable to achieve measurable improvement in professional practice and skills competency. The country specific demand for a needs-based pharmacy education reflects global trends but may also provide useful insights for individual transitions to transform education through practice and improve practice through education.